Penerapan Algoritma Negamax dan Alpha Beta Pruning pada Permainan Othello - William William; Regiza Giovanno; Daniel Udjulawa (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2016)
The game becoming a means of entertainment for leisure time for many people. One of them is the game Othello is a classic board game. The purpose of this study was to apply the algorithm Negamax and Alpha Beta Pruning Algorithms in Othello game as opposed to a player, as well as the extent of the time required by the opponent using that algorithm. With both of these algorithms cleverness in taking strategy by the computer in the game can be calculated with the grace period currently provides solutions against the player. This game was made using Phonegap framework. Artificial intelligence will be visible when the algorithm used for the process. Identification workflow of Algorithms Negamax and Alpha Beta Pruning provides overview of the time required by the computer to interact with the players. System development using prototyping methods. Results of testing the application of the algorithm Negamax and Algorithms Alpha Beta Pruning in the game